2018
DOI: 10.3889/oamjms.2018.307
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Virus Herpes Simplex Type 1 in Patients with Chronic Periodontal Disease

Abstract: BACKGROUND:Periodontal disease is an inflammatory-destructive condition of the supporting tissues of the teeth. Microorganisms found in the dental plaque were considered to be the primary local etiologic factor responsible for the periodontal destruction. It is also evident that herpes simplex viruses may have an impact in the etiopathogenesis of periodontal disease.AIM:This study has been made with the aim to analyse the prevalence of herpes simplex virus type 1 (HSV-1) in the dental plaque (supra- and subgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
(38 reference statements)
0
11
1
1
Order By: Relevance
“…These findings are consistent with those of Imbronito et al, 24 suggesting that CMV and Tannerella forsythia coinfection is more prevalent in patients with chronic periodontitis than in periodontally healthy individuals. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Regarding HSV, Kazi et al,12 detected the presence of HSV-1 and HSV-2 in patients with severe chronic periodontitis, reporting a prevalence of HSV-1 in 52% of the cases, and HSV-2 in 56%. In this review, HSV was the virus least studied in the articles, being found only in 10 publications, although, paradoxically, it has a prevalence of 40%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with those of Imbronito et al, 24 suggesting that CMV and Tannerella forsythia coinfection is more prevalent in patients with chronic periodontitis than in periodontally healthy individuals. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Regarding HSV, Kazi et al,12 detected the presence of HSV-1 and HSV-2 in patients with severe chronic periodontitis, reporting a prevalence of HSV-1 in 52% of the cases, and HSV-2 in 56%. In this review, HSV was the virus least studied in the articles, being found only in 10 publications, although, paradoxically, it has a prevalence of 40%.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CMV, a number of different studies support the presence and role of this virus in periodontal disease. 11,25 It infects different cell types and can undergo latency in the progenitor cells of macrophages, monocytes and Tannerella lymphocytes. 11,16 This virus shows a marked tropism for cells of the immune system and interferes with the innate, adaptive cellular and humoral immune response through the activation and silencing of natural killer cells (NK), decreasing and altering the presentation of MHC I and II complex antigens, thus interfering with apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ancient DNA (aDNA) has become an increasingly powerful tool for studying past infections, as massive parallel sequencing (NGS) has allowed for DNA libraries extracted from skeletal samples to be screened for thousands of microbial species (reviewed in Syprou et al 2019 30 ), shedding light on the evolutionary history and phylogeography of past infections. HSV-1 DNA is detectable in blood during a primary infection, but not during reactivation from latency 31 ; however, herpesvirus DNA and microRNA from non-primary infections have been recovered from the teeth 32 and subgingival plaque [33][34][35] of living individuals. HSV-1 DNA has also been recovered from the trigeminal ganglia of cadavers 12 indicating that it can reactivate peri-or post-mortem.…”
Section: Mainmentioning
confidence: 99%
“…HSV-1 has been found at higher prevalence in cases of chronic and aggressive periodontitis 34,35,38 , though the role in pathogenesis is inconclusive 38 . Both EDI111 and JDS005 have dental pathology consistent with periodontal disease (Supplementary Note 1).…”
Section: Recovery Of Ancient Hsv-1 Genomesmentioning
confidence: 99%